THE IMPACT OF ONLINE COLLABORATIVE LEARNING ON STUDENTS' ACADEMIC ENGAGEMENT IN SECONDARY SCHOOL CLASSROOM CONTEXTS - Inayatul Muntaqiyah; Syifa Zia Muharni (SENSEI RESEARCH CENTER, 2024)
Academic engagement is a critical factor in students' learning success because it reflects behavioral participation, cognitive investment, emotional involvement, and social interaction during learning. However, many students remain passive in online learning environments, particularly when digital activities are limited to individual assignments, teacher explanation, and one-way content delivery. Online collaborative learning offers an alternative by allowing students to interact, discuss ideas, construct knowledge, solve problems, and complete shared tasks through digital platforms. This study aims to examine the impact of online collaborative learning on students' academic engagement and to explore how students experience collaborative learning in digital environments. The study employed a mixed-method design using a quasi-experimental pretest-posttest control group approach supported by classroom observations, student interviews, reflective journals, and document analysis. The participants were 80 secondary school students divided into an experimental group and a control group. The experimental group received online collaborative learning activities through group discussion forums, shared documents, peer feedback, collaborative projects, and synchronous reflection sessions, while the control group received conventional online instruction. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, normalized gain scores, and effect size analysis, while qualitative data were analyzed thematically. The findings showed that online collaborative learning significantly improved students' academic engagement. Students improved in behavioral, cognitive, emotional, and social engagement through peer interaction, shared responsibility, task negotiation, feedback exchange, and group accountability. The study concludes that online collaborative learning can strengthen academic engagement when digital collaboration is structured, monitored, interactive, and supported by clear roles and assessment criteria.